Reoperations After Bariatric Surgery in 26 Years of Follow-up of the Swedish Obese Subjects Study - Hjorth, Stephan; Näslund, Ingmar; Andersson-Assarsson, Johanna C; Svensson, Per-Arne; Jacobson, Peter; Peltonen, Markku; Carlsson, Lena M S (JAMA surgery, 2019)
Bariatric surgery is an established treatment for obesity, but knowledge on the long-term incidence of revisional surgery is scarce. To determine the incidence and type of revisional surgery after bariatric surgery in 26 years of follow-up of participants in the Swedish Obese Subjects (SOS) study. The SOS study is a prospective nonrandomized controlled study comparing bariatric surgery (banding, vertical banded gastroplasty [VBG], and gastric bypass [GBP]) with usual care. The bariatric surgeries in the SOS study were conducted at 25 public surgical departments in Sweden. Men with body mass index values of 34 or higher and women with body mass indexes of 38 or higher were recruited to the surgery group of the SOS study between September 1, 1987, and January 31, 2001, and follow-up continued until December 31, 2014. Data analysis occurred from November 2016 to April 2018. Banding, VBG, or GBP. Revisional surgeries, analyzed using data from questionnaires, hospital records, and the Swedish National Patient register through December 31, 2014. A total of 2010 participants underwent surgery. The age range was 37 to 60 years. A total of 376 participants underwent banding (18.7%), while 1365 had VBG (67.9%) and 266 had GBP (13.2%). During a median follow-up of 19 years, 559 participants (27.8%) underwent first-time revisional surgery, including 354 conversions to other bariatric procedures (17.6%), 114 corrective surgeries (5.6%), and 91 reversals to normal anatomy (4.5%). Revisional surgeries (conversions, corrective surgery, and reversals) were common after banding (153 of 376 [40.7%]) and VBG (386 of 1365 [28.3%]) but relatively rare after GBP (20 of 266 [7.5%]). Patients who had banding and VBG primarily underwent conversions to GBP or reversals. Incidence of reversals was 5 times higher after banding than after VBG (40.7% vs 7.5%; unadjusted hazard ratio, 5.19 [95% CI, 3.43-7.87]; P < .001). Corrective surgeries were equally common irrespective of the index surgery (72 of 1365 patients who had VBG [5.3%]; 23 of 376 patients who had banding [6.1%]; 19 of 266 patients who had GBP [7.1%]). Revisional surgery indications, including inadequate weight loss, band-associated complications (migration, stenosis, and slippage), staple-line disruptions, and postsurgical morbidity, varied depending on index surgery subgroup. Most corrections occurred within the first 10 years, whereas conversions and reversals occurred over the entire follow-up period. Corrective surgeries occur mainly within the first 10 years and with similar incidences across all 3 surgical subgroups, but indications varied. Conversions (mainly to GBP) and reversals occurred after many years and were most frequent after banding and VBG, reflecting a higher overall revisional surgery demand after these operations.